MEASURING THE IMPACT OF DIGITAL TRANSFORMATION ON EFFICIENCY AND TRANSPARENCY: AN ANALYTICAL REVIEW OF OFFICIAL LEGISLATION AND REPORTS IN IRAQ FOR THE PERIOD (2020–2024) - ⁠ Lect. Alaa Jumaah Kareem (Modern American Journals, 2025)
Over the recent years, the digital transformation has been facing growing interests attributable to its role in enhancing achievement speed, relaxation of costs, bridging of data and information gaps, and providing oversight with a dominant role that contributes to the dimension of governance and maturity and finally to efficiency and transparency. Since 2020, Iraq has been among the countries that strive to transform digitally, and during the process, it has taken a series of measures and numerous channels. The research is expected to gauge the effectiveness of the government laws and governmental reports on efficiency and transparency through an analytical review methodology on laws and instructions presented in a sequence in both the state and given to the state and non-state organisations. It used the official sources of obtaining the required data and information such as the General Secretariat of the Council of Ministers, the Central Bank of Iraq, the Iraqi Ministry of Finance, the Federal Board of Supreme Audit, and the International Bank of Reconstruction and Development. The descriptive-analytical method was also used in the study wherein a review of legislation, instructions, and reports was done during the period (20202024). Moreover, it employed a methodology that transforms qualitative indicators into quantitative indicators on the (01) scale in order to compare and analyze them. The study concluded that digital period, despite being limited to specific areas and showing low effectiveness, was nevertheless influential in promoting efficiency and transparency. It also found that the Iraqi business environment remains unprepared to encourage both foreign and domestic investment. transformation in Iraq during the examined
Keywords: (Digital Transformation, Efficiency, Transparency, Official Reports, Governance, Maturity)